Sporogenous Probiotics, Iron Deficiency and Immunity - L.V. Kvashnina (Zaslavsky O.Yu., 2016)
The article presents an overview of current data about biological properties and characteristics of sporogenous bacteria Bacillus coagulans. Those data demonstrated efficacy and advantages of medical drug Lactovit Forte, which contains spores of Bacillus coagulans and vitamins В9 and В12. These results of proven effective impact on the immune system and hematopoiesis are based on the methods of evidence-based medicine.